Ernesta Foldāta piedzīvojumi Venecuēlā un dzeja par to - Kuzņecova, Kristīne (My University, 2019)
Latvijas Universitātes Goda doktora, Latvijas Zinātņu Akadēmijas Ārzemju Goda locekļa, Venecuēlas Centrālās Universitātes un Nacionālo parku institūta emeritētā profesora, orhideju pētnieka Ernesta Foldāta (1925-2003) apraksti par piedzīvojumiem Venecuēlā un dzeja par to.

Descriptions of his adventures in Venezuela and poetry about it by Ernest Foldat (1925-2003), an professor emeritus at the Central University of Venezuela and the Institute of National Parks of the University of Latvia, an honorary doctor of the Latvian Academy of Sciences, an honorary member of the Latvian Academy of Sciences.
Adventures of Ernest Foldat in Venezuela and poetry about it
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Plant physiology; Ernests Foldāts; Ernest Foldat; Venecuēla; Venezuela; piedzīvojumi; adventures; dzeja; poetry